Systematic review of lymphovenous anastomosis (LVA) for the treatment of lymphedema. Issue 8 (3rd October 2017) - Scaglioni, Mario F.; Fontein, Duveken B. Y.; Arvanitakis, Michael; Giovanoli, Pietro
Abstract : Introduction: Lymphedema is a chronic condition caused by the obstruction or impairment of lymphatic fluid transport resulting in irreversible skin fibrosis. Besides conservative therapy, surgical techniques for lymphedema including liposuction, lymphatico‐lymphatic bypass, lymphovenous anastomosis (LVA), and vascularized lymph node transfer (VLNT) are options with increasing popularity in the recent past. In our review, we investigated the efficacy of LVA for the treatment of lymphedema. Both objective and subjective outcomes of surgical treatment were evaluated. Methods: Studies were identified through systematic review in PubMed database up to September 2016. Only original Articles which exclusively performed LVA for lymphedema treatment were included. Our primary endpoint was the objective of a subjective postoperative lymphedema reduction. Results: A total of 293 titles were identified, out of which 18 studies including 939 patients were deemed eligible. The studies included in this review describe significant variations in surgical techniques, number of anastomoses and supplementary interventions. All studies reported objective reductions in circumference measurements. Subjective symptom relief was found in 50‐100% of the patients as well as a reduction in the number of cellulitis episodes in all investigated cases. Conclusion: Although the studies included in this review showed great heterogeneity, LVA surgery revealed both objective and subjective improvements in most patients.